A conceptual introduction to chemistry - Bauer, Richard C. (McGraw-Hill Higher Education, 2007)
A Conceptual Introduction to Chemistry by Bauer/Birk/Marks offers today’s student a fresh perspective to the introduction of chemistry. This new textbook offers a conceptual approach to chemistry by starting first with macroscopic phenomena, and then presenting the underlying microscopic detail. Each chapter opens with a real-life scenario that helps students connect abstract chemical concepts to their own lives. The math found in A Conceptual Introduction to Chemistry is introduced on a need-to-know basis, with "Math Toolboxes" ending each chapter, in support of the math skills required in that chapter.